2016
DOI: 10.24925/turjaf.v4i5.378-383.637
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Adoption of Recommended Cauliflower Production Technology in Nepal

Abstract: Binary logit regression model of econometrics was used to identify the factors affecting adoption of recommended agricultural technology by the commercial farmers of Nepal. A survey was carried out in 2012 in 120 households from Kavre district, Nepal. The objective was to appraise factors affecting adoption of recommended technology of cauliflower, finding out the level of adoption, identifying the constraints of cauliflower cultivation, assessing the perceived level of satisfaction and studying the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
(1 reference statement)
2
9
0
Order By: Relevance
“…This implies that rice farmers who were educated as well as had adequate information and available complementary inputs were in the best position to decipher information and comprehend the economic incentiveshigher yields, increased profits, and greater sustainabilityof improved rice varieties, leading to adoption. The findings are consistent with previous studies (Dhital and Joshi, 2016;Ghimire et al, 2015;Mittal, and Mehar, 2016) that found education, farm size, extension services and seed access to influence the adoption of improved technologies.…”
Section: Determinants Of Adoption Of the Technology Bundlessupporting
confidence: 92%
See 1 more Smart Citation
“…This implies that rice farmers who were educated as well as had adequate information and available complementary inputs were in the best position to decipher information and comprehend the economic incentiveshigher yields, increased profits, and greater sustainabilityof improved rice varieties, leading to adoption. The findings are consistent with previous studies (Dhital and Joshi, 2016;Ghimire et al, 2015;Mittal, and Mehar, 2016) that found education, farm size, extension services and seed access to influence the adoption of improved technologies.…”
Section: Determinants Of Adoption Of the Technology Bundlessupporting
confidence: 92%
“…Several farm, farmer, and socio-economic characteristics have featured extensively in both the theoretical and empirical literature in explaining farmers' adoption decisions. Farmer's age, farm size, education, on-farm/off-farm income, extension contact, and access to credit have been found to be significantly related to the adoption of agricultural technologies (Dhital and Joshi, 2016;Ghimire et al, 2015;Mittal and Mehar, 2016;Simtowe et al, 2016). However, most existing studies have limited the measurement of smallholder farmers' adoption choice to a single technology, such as an improved variety or fertilizer (Ghimire et al, 2015;Simtowe et al, 2016) while only a few studies have focused on two or more technologies (Abay et al, 2016;Mittal and Mehar, 2016;Yirga et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Experience of large cardamom had positive impact on improved drying (p <0.1) and curing (p <0.05) whereas it had negative impact on cleaning (p <0.1) and grading (p <0.05). Farming experience was found to be positively associated with adoption of new recommended practice (Dhital & Joshi, 2016). Ekepu and Tirivanhu (2016) reported that farming experience showed no significant effect on adoption decisions of agriculture technologies.…”
Section: Opportunities Threatsmentioning
confidence: 96%
“…Many literature showed the positive relationship of membership in any organizations and farmers decision to adopt new technologies (Dhital & Joshi, 2016;Katungi & Akankwasa, 2010;Subedi et al, 2019). Farmers in group tend to come together with a commitment and with sense of direction and plan for the future.…”
Section: Opportunities Threatsmentioning
confidence: 99%
See 1 more Smart Citation